A new design and performance optimization of bio-inspired flexible protective equipment. (11th September 2020) - Zhang, Chaohui; Rawat, Prashant; Liu, Peng; Zhu, Deju
Abstract: In this study, a new biomimetic design of protective equipment has been proposed. Basically, teleost fish scales combine a two-layered structure, a tough high mineralized bony layer with a relatively soft collagen and fiber-based sublayer arranged in a periodic overlapping design, which offers excellent flexibility and puncture resistance. For the biomimetic design of fish scales, a hard-ceramic layer with an ultra-high-molecular-weight polyethylene based-sublayer is used for the design of protective equipment. Finite element analysis of the bio-inspired protective design and its ballistic performance is done by a commercially available 3D simulation software LS-DYNA. Various design parameters, including the overlapping angle of adjacent scales, frictional coefficient between scales, number of Kevlar layers in the backing layer, ceramic types in the scale are discussed and analyzed to optimize the flexibility aspects of protective equipment. The ballistic performance of newly designed protective equipment with a failure pattern is examined as per the National Institute of Justice (NIJ) standards level III. Results based on experimental outcome and optimized parameters defined the critical performance limit of the protective equipment. Therefore, the results of this research provide valuable information related to ballistic safety equipment for improving the existing designs and/or fabricating innovative protective equipment.